2022
DOI: 10.1111/bjd.21704
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of inflammatory bowel disease in patients with chronic inflammatory skin diseases: a cohort study

Abstract: Background Several studies have linked various chronic inflammatory skin diseases (CISDs) with inflammatory bowel disease (IBD) in a range of data sources with mixed conclusions. Objectives We compared the incidence of IBDulcerative colitis (UC) and Crohn disease (CD)in patients with a CISD vs. similar persons without a CISD. Methods In this cohort study using nationwide, longitudinal, commercial insurance claims data from the USA, we identified adults and children who were seen by a dermatologist between 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…The worldwide prevalence of HS is estimated at about 1% [ 1 ]. HS is associated with numerous comorbidities including metabolic syndrome, spondyloarthritis, inflammatory bowel disease as well as non-alcoholic fatty liver disease (NAFLD), and is therefore seen as a systemic disease [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Importantly, the number of concomitant diseases correlates with the duration from manifestation of first symptoms until HS diagnosis [ 12 ].…”
Section: Hidradenitis Suppurativa—a Debilitating Disease With High Me...mentioning
confidence: 99%
“…The worldwide prevalence of HS is estimated at about 1% [ 1 ]. HS is associated with numerous comorbidities including metabolic syndrome, spondyloarthritis, inflammatory bowel disease as well as non-alcoholic fatty liver disease (NAFLD), and is therefore seen as a systemic disease [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Importantly, the number of concomitant diseases correlates with the duration from manifestation of first symptoms until HS diagnosis [ 12 ].…”
Section: Hidradenitis Suppurativa—a Debilitating Disease With High Me...mentioning
confidence: 99%
“…In a recent nationwide cohort study, HS was significantly associated with an increased risk of CD (HR CD =1.23; 1.03-1.46) but not UC (HR UC =1.01; 0.89-1.14). 53 Given the significant comorbidity associated with this condition, it is unsurprising that a recent systematic review of 12 epidemiological studies noted that sexual dysfunction was significantly increased in HS patients. 54 Vulvovaginal Side-Effects of IBD Specific Therapy Immunosuppressive therapy with azathioprine, 6-mercaptopurine, and anti-TNF biologics have been linked to an increase in certain infections, which in turn can lead to vulvovaginal lesions.…”
Section: Extraintestinal Manifestations Of Ibdmentioning
confidence: 99%
“…In a recent nationwide cohort study, HS was significantly associated with an increased risk of CD (HR CD =1.23; 1.03–1.46) but not UC (HR UC =1.01; 0.89–1.14). 53 Given the significant comorbidity associated with this condition, it is unsurprising that a recent systematic review of 12 epidemiological studies noted that sexual dysfunction was significantly increased in HS patients. 54…”
Section: Introductionmentioning
confidence: 99%
“…Hidradenitis suppurativa (HS) and Crohn disease (CD) are chronic, recurrent, inflammatory disorders with shared genetic susceptibility and immunologic features. Population-based studies have found an association between CD and HS in adults; however, this association is poorly characterized among pediatric patients. Herein we compared the prevalence of CD among pediatric patients with and without HS.…”
mentioning
confidence: 99%